Resilience of Indonesia’s Trade Balance to Short-Term Exchange Rate and Inflation Dynamics - Andreas Panjaitan; Suny Sabila; Septri Anisa; Debora Silvia Hutagalung; Artha Putri Br Karo (Economic: Journal Economic and Business, 2025)
Indonesia's trade balance is often considered vulnerable to exchange rate fluctuations and inflation, but in reality, the period from January 2023 to December 2024 showed a surprising pattern. This study uses a quantitative approach with multiple linear regression on monthly data from Bank Indonesia and Statistics Indonesia to examine the short-term effects of the exchange rate and inflation. The results show that neither is significantly affected. Despite a moderate depreciation of the rupiah and a decline in inflation to its lowest level in history, the trade balance remains in surplus. This finding challenges the common assumption that short-term macroeconomic fluctuations determine trade performance and reveals that structural external factors such as global commodity prices and trading partner demand play a more dominant role. This study emphasizes the need for innovative sector-based trade strategies beyond conventional monetary instruments to maintain external stability.